The Role of Tax Enforcement and Compliance Activities in Mitigating the Tax Gap - Sinha, Sushma (Journal of Global Economy, Business and Finance, 2025)
This study presents an empirical analysis of the role of tax enforcement and compliance activities in minimizing the tax gap in the United States of America. To identify the influence of tax enforcement and compliance activities on tax gap, the author used a regression model where tax gap was utilized as the dependent variable, and the ratio of tax return examined to total tax return filed utilized as the independent variables; between 2008 and 2021. The result of the regression analysis evidenced that tax gap is influenced by the extent of tax enforcement and compliance activities. The conclusion reached also entails that it is imperative for policymakers to guarantee that the IRS has sufficient funding and resources to efficiently execute its tasks; thereby increasing tax examinations and reducing tax gap.